Analisis Faktor Perilaku Konsumen terhadap Atribut Produk dalam Keputusan Pembelian Food Consumer Product - Djamaris, Aurino RA (Business and Management Review, 2012)
This research is to identify the factors which determine consumer purchase decision process on food consumer products (menthol cigarette), identifies the attributes that are considered important by consumers on food products consumer products, and analyze consumer attitudes on the attributes of consumer products food products. The study used primary data obtained from consumer  of  food consumer product  that  ever or used products available on the market (supermarkets etc) analyzed using factor analysis and  analysis of  consumer  attitude  using Fishbein Multi-Attributes approach.  The results showed that there are seven factors derived from 19 variables known to determine a person's  purchase  decision process  of  food consumer products. In the analysis of the attitudes found that nine attributes of the food consumer products fully considered  and deemed important by consumers, enthol flavor attributes are the most important attributes in buying a food consumer productby consumers.    The data were collected from individual  that were willing to participate in the study and not randomly selected; the possibility that the samples were atypical of a more general population exists. This study reviewed only by the theory of marketing and the theory of consumer behavior (non-marketing).    The factors found and the attributes that are considered most important products can assist manufacturers in identifying what is actually desired by consumers.Management interest in  purchase decision  of  a food consumer product by consumersshould pay attention to  menthol flavor attributes the most important attributes in  purchase decision.  By revealing the value factors associated with Consumer Behavior on Purchase Decision Attributes of Food  Consumer  Products, the study contributes to richer understanding of what factors should be considered on attributes of food consumer  product purchase decision . Keywords: Purchase Decision, Customer Behavior, Factor Analysis, Product Atribute, Menthol Cigarette